Meaning of Phrasal Verb ‘pick up’ Subtype do/happen: A Natural Semantic Metalanguage Approach - Luh Gde Inten Purnama Sari Setiawan; L. Sutjiati Beratha; Ni Wayan Sukarini (The Doctoral Studies Program of Linguistics of Udayana University, 2019)
The difficulties in knowing and understanding the meaning of a language oftenappear in units of language with an idiomatic meaning, such as phrasal verb. A single unit ofphrasal verb usually produces a meaning which is totally different with the meaning of itsconstituent. Phrasal verb ‘pick up’ is a unique phrasal verb since it bears various meaningsunlike other phrasal verbs. The implementation of Natural Semantic Metalanguage (NSM) as atheory in this study leads to a great significance of avoiding misunderstanding on the meaningsof phrasal verb ‘pick up’ by defining the meanings through semantic structures. This study isintended to find and describe the meanings of phrasal verb ‘pick up’. Mention the object of thestudy here result of this study showed that phrasal verb ‘pick up’ is a kind of transitive phrasalverb which often followed by object. The different objects in phrasal verb ‘pick up’ lead to non-composition polysemi between DO / HAPPEN. This combination of two polysemies come ineight meanings.